Ultrasonic vibration - assisted pelleting and dilute acid pretreatment of cellulosic biomass for biofuel manufacturing - Song, Xiaoxu (Kansas State University, 2015)
In the U.S. and many other countries, the transportation sector is almost entirely dependent on petroleum-based fuels. In 2011, half of the petroleum used in the U.S. was imported. The dependence on foreign petroleum is a real threat to national energy security. Furthermore, the transportation sector is responsible for about 30% of U.S. greenhouse gas emissions and is growing faster than any other major economic sector. National energy security, economy, environment sustainability are all driving the U.S. to develop alternative liquid transportation fuels that are domestically produced and environmentally friendly. Promoting biofuel is one of the efforts to reduce the use of petroleum-based fuels in the transportation sector. Cellulosic biomass are abundant and diverse. Thus, the ability to produce biofuel from cellulosic biomass will be a key to making ethanol competitive with petroleum-based fuels. Ultrasonic vibration- assisted (UV-A) pelleting can increase not only the density of cellulosic biomass but also the sugar yield. This PhD dissertation consists of fourteen chapters. Firstly, an introduction of the research is given in Chapter 1. Chapters 2, 3, 4, and 5 present experimental investigations on effects of input variables in UV-A pelleting on pellet quality. Chapter 6 investigates effects of input variables on energy consumption in UV-A pelleting. Chapter 7 develops a predictive model for energy consumption in UV-A pelleting using the response surface method. Chapter 8 investigates effects of input variables on energy consumption, water usage, sugar yield, and pretreatment energy efficiency in dilute acid pretreatment. Chapter 9 develops a predictive model for energy consumption in dilute acid pretreatment using the response surface method. Chapter 10 studies ultrasonic vibration-assisted (UV-A) dilute acid pretreatment of poplar wood for biofuel manufacturing. Chapter 11 compares sugar yields in terms of total sugar yield and enzymatic hydrolysis sugar yield between two kinds of materials: pellets processed by UV-A pelleting and biomass not processed by UV-A pelleting in terms of total sugar yield and enzymatic hydrolysis sugar yield. Chapter 12 develops a physics-based temperature model to predict temperature in UV-A pelleting. Chapter 13 develops a physics-based density model to predict pellet density in UV-A pelleting. Finally, conclusions and contributions of this research are summarized in Chapter 14.
Keywords: Biofuel; Biomass; Density; Pelleting; Temperature; Modeling; Industrial Engineering (0546)